Evaluation of workload and its impact on satisfaction among pharmacy academicians in Southern India - Akram, Ahmad; Khan, Muhammad Umair; Srikanth, Akshaya B.; Patel, Isha; Nagappa, Anantha Naik; Jamshed, Shazia Qasim (JCDR Research and Publications (Pvt) Limited, 2015)
Objective: The purpose of this study was to determine the level of workload among pharmacy academicians working in public and private sector universities in India. The study also aimed to assess the satisfaction of academicians towards their workload.